PENINGKATAN KEEFEKTIVAN PEMANFAATAN DANA BOS SMP MELALUI IMPLEMENTASI SISTEM ANALYTIC HIERARCHY PROCESS (AHP) - Trisno Martono Martono; Salman Alfarisy Totalia; Baedhowi Baedhowi; Hery Sawiji; Budi Wahyono; Dini Octoria (Department of Economics Education, Universitas Sebelas Maret, 2024)
There are still many junior high schools that have not been able to optimize the use of BOS funds, including Pangkur 1 Public Middle School, Kec. Pangkur, Ngawi. The main problem faced by SMP Negeri 1 Pangkur Ngawi is that they have not been able to set a priority scale in using the BOS funds for the 10 targets that have been determined in Permendikbud Number 3 of 2019. So the targets are made only to make it easier to make accountability reports not on school needs.The solution offered through this community service activity is to hold training on determining the priority scale for the use of BOS funds using the Analytical Hierarchy Process (AHP) system. AHP is a decision support model developed by Thomas L. Saaty. AHP is used to make a sequence of alternative decisions and choose the best for the decision maker. So far, many schools have not been able to determine the alternative target sequence for the BOS funds to be obtained, so that the use of BOS is not optimal. Optimization of the determination of the alternative sequence of BOS targets can be carried out using the AHP system. This activity was aimed at providing training for the elementary school BOS management team so they could use the AHP system to optimize the use of BOS funds.